2019
DOI: 10.1007/s10680-019-09541-0
|View full text |Cite
|
Sign up to set email alerts
|

Declined Total Fertility Rate Among Immigrants and the Role of Newly Arrived Women in Norway

Abstract: In many Western countries, the total fertility rate (TFR) of immigrant women has declined over the last decades. This paper proposes two methods for investigating such changes in the aggregate immigrant fertility level: what-if scenarios and a formal decomposition. Both methods disentangle the effect of changed composition-by origin area and duration of stay-from the effect of changed fertility within subgroups. The methods are applied to data from Norway, where immigrant TFR declined from 2.6 births per women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
1
7
0
1
Order By: Relevance
“…In previous research, immigrant women's fertility is often found to be relatively high after arrival but declining by duration of stay (Mayer and Riphahn 2000;Bélanger and Gilbert 2002;Andersson 2004;Sobotka 2008;and Tønnessen 2019). To explain patterns in immigrant fertility, the literature offers hypotheses of adaptation, socialization, selection, disruption, and interrelation of events (see Kulu 2005;Milewski 2010;Wilson 2015; or Adserà and Ferrer 2015 for comprehensive overviews).…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, immigrant women's fertility is often found to be relatively high after arrival but declining by duration of stay (Mayer and Riphahn 2000;Bélanger and Gilbert 2002;Andersson 2004;Sobotka 2008;and Tønnessen 2019). To explain patterns in immigrant fertility, the literature offers hypotheses of adaptation, socialization, selection, disruption, and interrelation of events (see Kulu 2005;Milewski 2010;Wilson 2015; or Adserà and Ferrer 2015 for comprehensive overviews).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 thus generates insights about the role of year of arrival (birth cohort + age at arrival) in determining immigrant fertility. As we have argued elsewhere, such evidence points towards the importance of explanations that relate to year of arrival (Tønnessen 2019), which include period fluctuations in migration policies, changes in origin-country fertility norms (and childhood socialisation), as well as changes in the selectivity and composition of immigration to Norway. Thus, the reduced steepness of the slopes for younger cohorts also conveys information about changing period fertility-and over the last decades, the period TFR for immigrants in Norway has declined (Tønnessen 2019).…”
Section: Empirical Examples Using Register Datamentioning
confidence: 65%
“…In European countries with high immigration rates, migrants from higher fertility countries often retain higher fertility patterns in their host countries, and give a minor boost to the fertility rates in those countries (Sobotka 2008;Tønnessen 2019). In addition, migration among women is often interrelated with childbearing (see Andersson in this volume).…”
Section: Fertility Trends: the Shift Towards Unstable Delayed And Sub-replacement Fertilitymentioning
confidence: 99%